From Transactions to Relationships: Leveraging E-Service Quality to Secure E-Customer Trust and Loyalty - Rahman Utami, Siti Yolanda; Yulianto, Edy; Luthfi Imam Fahrudi, Agung Nugroho (FIA UB, 2024)
This research explores the interconnected relationship between e-service quality, customer trust, and loyalty in the context of Indonesian e-commerce, focusing specifically on the Shopee platform. Analyzing data from 279 Shopee users, the study examines the influence of website design, customer service, security, and fulfillment on e-service quality and their subsequent impact on trust and loyalty. Employing a purposive sampling approach and SEM-PLS inferential analysis, the findings reveal the significant impact of website design on shaping e-service quality. At the same time, customer service and security do not show significant effects. Interestingly, efficient fulfillment emerges as a critical determinant in boosting e-service quality. The study further emphasizes the significant role of e-service quality in fostering customer loyalty, both directly and indirectly, through the mediation of e-customer trust. These insights provide actionable takeaways for e-commerce players, paving the way for strategic maneuvers and sustained success in Indonesia's competitive e-commerce market.